Rotamerization equilibrium in novel N,N-disubstituted chloroacetamides: An NMR spectroscopic study - Fraga, Guido Gustavo (2022)
We studied the E/Z rotamers of new N-substituted 2–chloro-N-(2-nitrobenzyl)acetamides by applying 1HNMR and 13C-NMR techniques. The restricted rotation around the amide bond generates a mixture of E/Z diastereomers visualized as a set of appreciably separated signals in the NMR spectra. In order to assign each signal to its corresponding rotamer, the criterion of the anisotropic solvent-induced shift (ASIS) effect, observed in the 1H-NMR spectra, was used. The effects of solvent and substituent on the relative E/Z ratios were also analyzed.